Sound Velocities of the Hydrous Iron‐Rich HH1‐Phase: Implications for Lower Mantle Seismic Heterogeneities - Lu Liu; Alfred Q. R. Baron; Eiji Ohtani; Hiroshi Fukui; Daijo Ikuta; Daisuke Ishikawa; Li Zhang (Geophysical Research Letters)
Abstract We investigated the compressional and shear velocities, VP and VS, of the HH1‐phase by combining the inelastic x‐ray scattering and x‐ray diffraction experiments. In the pressure range of 64.7–79.6 GPa and at room temperature, the VP and VS were measured to be 9.66–11.05 and 4.9–6.4 km·s⁻1, respectively. We employed a simplified model to quantitatively discuss the sound velocity differences between hydrous and anhydrous phase assemblages in the mid‐lower mantle, revealing that the hydrous assemblage exhibits increased VS and a reduced VP/VS ratio compared to its anhydrous counterpart. This suggests formation of seismic scatterers in the mid‐lower mantle exhibiting high VS anomalies may be related to the heterogeneous distribution of water. Moreover, the interpretation of a large VP/VS ratio as indicating the presence of water in the upper mantle and crust may not be applicable for detecting water in the lower mantle.